Inhibitors Element of Bumdes in Promoting Rural Resilience in Indonesia - Kusmulyono, Muhammad Setiawan; Dhewanto, Wawan; Famiola, Melia (International Research Journal of Business Studies, 2021)
Rural has become a prime headline for Indonesia’s development since the enactment of the Rural Act in 2014. Since the ratification, rural governments in Indonesia have more authority to manage their village economy through the establishment of a village-owned social enterprise (VOSE). In 2019, 45,549 VOSEs were established from the total of 83,931 villages in Indonesia. Unfortunately, although several VOSEs show good performance, most have problems that hamper their growth. This article stems from the researchers’ desire to observe the contribution of entrepreneurial activities in the village to rural resilience. This research applied qualitative research by interviewing rural stakeholders in nine Bumdes. The findings of the study indicate that low commitment from village heads and Bumdes directors, low motivation from Bumdes management, inadequate business knowledge from Bumdes management, rural political dynamics, and fluctuations in community participation are all obstacles to Bumdes’ ability to promote rural resilience. This research demonstrates that in order to attain rural resilience, Bumdes requires a more holistic strategy to promote stakeholder attachment.